The Agendas of The Stream (2014)
The new tech has introduced the traits of the hypermedia, interactivity and convergence in the journalism field. Moreover, it has involved the emergence of new media and changes in the informative contents. In 2006 Al Jazeera in English was created for covering the underreported regions, inasmuch as new media arise, new contents do so, thus, the research examines the agendas of The Stream, the TV show from Al Jazeera that relies heavily on social networks.